Peningkatan Literasi Keuangan Syariah Bagi Guru Perbankan Syariah - Khasan Setiaji; Ubaedul Mustofa; Muhammad Feriady (Universitas Lancang Kuning, 2020)
The sharia banking expertise program at SMK is getting developed. However, it has not been fully supported by the availability of competent teachers. That is because the teachers do not come from finance or sharia banking graduates. Having that phenomena, a sharia banking training was conducted. The partners in this activity are the MGMP Central Java and DIY Sharia Banking. The participants are 44 teachers. Before the training, a pre-test was conducted with the average score of 63.11 for each participant. After having the test, a post test was obtained with an average score of 77.07. Based on the Difference Test, it can be seen that the significance value (Sig. (2-tailed)) of 0,000 is less than 0.05. In short, it can be concluded that there are significant differences in the competence of sharia banking teachers before training and after the implementation of sharia financial training.